Imbibition and temperature to rupture latency of Ischaemum rugosum Salisb - Portuguez-García, Mary Pamela; Rodríguez-Ruiz, Ana María; Porras-Martínez, Carolina; González-Lutz, María Isabel (Agronomía Mesoamericana, 2020)
Introduction. The germination of Ischaemum rugosum Salisb. is uneven due to the presence of latency, a process that affects its management and research. Objective. To evaluate three methods for breaking dormancy in I. rugosum Salisb. seeds that allow its uniform germination under controlled conditions. Materials and methods. Three experiments were carried out at the Laboratorio Oficial de Análisis de Calidad de Semillas del Centro para Investigaciones en Granos y Semillas of the Universidad de Costa Rica, San José, Costa Rica; from May to June 2016. In the first experiment, potassium nitrate and distilled water, two imbibition times, and a control without imbibition were tested. In the second, the seeds were subjected for three weeks to four constant temperature regimes (15 °C, 30 °C, alternating temperatures 15 and 30 °C, and ambient temperature of 26 °C). In the third, seeds were placed in water for one hour at different degrees of heat (23, 30, 45, and 65 °C), a control without imbibition was used. Results. In the first experiment, the best treatments were 16 and 24 h of imbibition with potassium nitrate. In the second experiment temperature was a significant factor, germination was reached with three temperatures used, only with 15 °C there was no germination. In the third experiment the temperature in the water was a significant factor, the highest germination occurred in the treatment at 23 °C, while at 65 °C no germination occurred. Conclusion. The use of hot water as a way to break latency was ruled out. It is concluded that the best treatments were KNO3 at 0.25 % for 16 or 24 h, while the use of water was only effective in the time of 16 h, in all three cases alternating temperatures between 15 and 30 ° C.